Revisiting the neuroscientific evidence for unconscious perception - the implications of affordances theory and biased competition - Ivaylo Borislavov Iotchev; Hein Thomas van Schie (Acta Psychologica, 2025)
Neuroscientific support for the equivalence hypothesis, stating that perception can be either conscious or unconscious, rests upon overlap in the brain areas activated during conscious perception and subliminal priming. This interpretation is argued here incompatible with the implications of the biased competition model, wherein different interpretations of the world compete and one must be suppressed in favor of the other. In such a framework a representation should not only be defined by what information is active, but also by what information is suppressed. Currently there is no reason to believe that the content of primes can suppress alternative interpretations of reality. The implications of biased competition elegantly explain why primes often merely bias the agent, instead of being real targets for behavior. Our theoretical proposal awaits further empirical investigation.